Interaction studies through character association, divergence and coefficient of variation in chrysanthemum (Chrysanthemum morifolium) - BALA, MADHU; SINGH, MOHINI PRABHA; REHANA, SHAIK (The Indian Journal of Agricultural Sciences, 2026)
Chrysanthemum morifolium (Ramat.) holds one of the most pertinent constituents of global floriculture market. The study was carried out during 2021–22 and 2022–23 at Punjab Agricultural University, Ludhiana, Punjab to categorise diverse chrysanthemum genotypes based on their response groups, morphological variability and their selection for breeding new genotypes. The present investigations comprehensively assessed the morphological parameters of 20 chrysanthemum genotypes collected from leading Indian research institutes across cut, loose and pot genotypes. Coefficient of variance, heritability, genetic advance and path coefficient analysis were done. Analysis of variance revealed significant responses in different morphological, floral and reproductive traits. A high coefficient of variation (>20%), heritability and genetic advance were revealed in flower number/plant (FN), number of ray florets, thickness of ray florets, plant height, days to 50% flowering accounting a significant genetic control. Plant height showed maximum positive correlations with most of traits. High heritability with regard to flower number, ray florets, days to flower opening, plant height and spread except for primary branches. The high value of genetic advance was recorded for traits; number of ray florets and flower number demonstrating that after choosing the top 5% high yielding genotypes as parents, the traits in a new generation can increase significantly. Path coefficient attributed nine traits as positive and seven traits as negative with direct effects on number of flowers/plant. The findings highlighted the importance of integrated trait selection strategies to develop high-performing chrysanthemum cultivars with enhanced ornamental value and adaptability to diverse growing conditions.